Assessing The Vegetation Degradation Dynamics in Salt Mine Areas of District Chakwal, Pakistan - Ghulam, Rehana; Siddiqui, Saima (Pakistan Journal of Humanities and Social Sciences, 2023)
The sustainability of human habitation is seriously threatened by land degradation and it is crucial to evaluate it quantitatively. This study aims to identify the spatiotemporal trends and vegetation degradation dynamics in the salt mine area of district Chakwal, Pakistan. One of the abandoned mines, the Chakwal salt mine, experienced subsidence as a result of the pillars dissolving from unmanaged leaching processes, which produced a large cavern in a horizontal direction. Changes in vegetation cover are influenced by the phenomenon of land deformation (landslides and subsidence). The goal of the current study is to employ multi-spectral remote sensing data to analyze the temporal alterations in vegetation brought on by salt mining. The study used Landsat-derived NDVI to model vegetation degradation dynamics over 30 years (1990–2020). The normalized difference vegetation index (NDVI), leaf area specific index (SLAVI), normalized difference water index (NDWI), and thermal index were used in the current investigation to construct detailed maps of the vegetation. The zones affected by land degradation, which has a direct impact on vegetation covering, are identified using the change detection approach in vectorial format on NDVI and all other factor data. As a result, an analysis of the NDVI for vegetation demonstrates that there has been a drastic decline from 0.5973 to 0.4321 between 1990 and 2020. The outcomes supported the viability of assessing the vegetation growing status in the salt mining area using remote sensing technology. Furthermore, the government must act right away to implement several prudent policies that will position it in the best possible position once the current environmental crisis has passed.